Effect of the experimental parameters on the structure of nitrogen-doped carbon nanotubes produced by aerosol chemical vapour deposition - Koós, A; Dowling, M; Jurkschat, K; Crossley, A; Grobert, N (2009)
We describe the systematic study of multi-walled carbon nanotubes with different nitrogen doping produced by aerosol chemical vapor deposition. Benzylamine:toluene mixtures of 0:100, 5:95, 10:90, 25:75, 50:50, 75:25 and 100:0 were thermally decomposed at 800-900 °C under argon at atmospheric pressure, whereby the nitrogen content of the bulk material was varied between 0 and 2.2 at%. We also show how the presence of nitrogen in the precursor changed the nanotube morphology, i.e. nitrogen decreased the number of kinks incorporated into the carbon nanotubes, decreased their length and diameter and increased the proportion of 'bamboo' shaped nanotubes. Furthermore, due to the nitrogen doping, the oxidation resistance of the nanotube material was decreased. With concentrations above 10% benzylamine the increase of the reaction temperature had no significant effect on the quality of the nanotubes, however, at higher temperatures the nitrogen content was decreased. We demonstrate the control over the nanotube geometry, the nitrogen content and oxidation resistance of the nanotubes, and show that these properties are interlinked. © 2008 Elsevier Ltd. All rights reserved.